Reduced Lithium/Nickel Disorder Degree of Sodium‐Doped Lithium‐Rich Layered Oxides for Cathode Materials: Experiments and Calculations. Issue 1 (7th January 2020) - Hu, Yongyuan; Qin, Zhongzheng; Pei, Jian; Cong, Bowen; Yang, Xu; Chen, Gang
Abstract: Sluggish kinetics and poor electrochemical stability limit the implications of Li‐rich layered oxide cathode materials, which are regarded as one of the most promising potential cathode materials for lithium‐ion batteries. In this work, a Na‐doped Li‐rich layered oxide (abbreviated as N‐LLO) cathode material is prepared through co‐precipitation combined with calcination. During the annealing process, partial Li2 CO3 is substituted by Na2 CO3, which helps to optimize the primary particles and realize Na doping. The obtained N‐LLO cathode exhibits a greater specific capacity and excellent rate performance. The characterization and DFT calculations suggest that the doped Na ions could reduce the formation of Li/Ni disorder defects, change local bond length, and enlarge Li interslab spacing conducive to Li‐ion diffusion, improving the rate performance. Abstract : Ordering the disorder : Doping with sodium (Na) ions makes the Ni−O bonds and the average bond lengths in different locations diverged, and suppresses the formation of Li/Ni disorder defects.